Editorial: The need for South African (higher) education institutions to be attuned to Education 4.0 - Waghid, Z. (South African Journal of Higher Education, 2019)
Higher education institutions in South Africa continue to face uncomfortable positions. These uncomfortable positions started with the #fallist movement – an alter-globalisation movement that argues for the decolonisation of the knowledge spheres in South African higher education to place African knowledge at the centre of learning. With the #fallist movement’s rhetoric forcing university academics to adapt the curriculum, content, methodologies and pedagogies aligned to the African experience through research and various platforms, the global context has already begun to shift towards the fourth industrial revolution. This shift towards the fourth industrial revolution thus places South African higher education institutions in an uncomfortable position of having to adapt teaching methodologies and pedagogies in line with the global context (Waghid, Waghid & Waghid 2018).